The Ladies of Long: how a group of non-gender normative youth construct their identity and perform gender - Strimenos, Alexis (Gender Studies, 2014)
This body of text is the product of an ethnographic study, conducted on (or more appropriately, with) a particular group of non-gender normative persons, interrogating the question of how they construct their own identity and perform gender? I argue that one could not effectively take on this project without simultaneously interrogating the category it purports to describe, and thus this piece proves to be as much an ethnography on gender as an ethnography on doing gender ethnography. Therefore, what is presented here is a demonstration of the value of this ethnography to contribute to a greater body of knowledge as it generates a nuanced and practical relational understanding of these otherwise seemingly intangible and highly ideational concepts, ambiguously termed gender and identity. This work also interrogates and engages deeply with notions of sexuality, subjectivity, agency, and personhood, examining the relationship and validity between abstract theory and reality, as it is revealed through an analysis of the articulations and observations of these unique individuals. Furthermore, as this offers more than a nuanced understanding of gender and identity in these people's lives, but an understanding of gender that extends beyond the specific scope of this question, the findings presented here, offer monumental insight and opportunity to sift through the leading contemporary theories foregrounding gender studies specifically that of Judith Butler's, Performativity Theory. And finally, as this work is built on the foundation of a feminist objective epistemology, it will prove also to be an articulation of the importance of methodology, demonstrating the significance of a study's methodology to be parallel to its findings. But most importantly this text will provide an in-depth description and analysis of the meanings and makings of gender, sexuality, and personhood in the context of a very particular social world, demonstrating the surprisingly profound agency these persons creatively practice in the constitution of their selves.